2019
DOI: 10.4049/immunohorizons.1900042
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Changes in Regional Lung Macrophages Are Associated with Metabolic Differences

Abstract: A number of pulmonary diseases occur with upper lobe predominance, including cystic fibrosis and smoking-related chronic obstructive pulmonary disease. In the healthy lung, several physiologic and metabolic factors exhibit disparity when comparing the upper lobe of the lung to lower lobe, including differences in oxygenation, ventilation, lymphatic flow, pH, and blood flow. In this study, we asked whether these regional differences in the lung are associated with DNA methylation changes in lung macrophages tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…AM are an important defense cell when viral or bacterial organisms invade deep into the lung to orchestrate the initiation and resolution of the immune response. AM maintain various effector functions, such as tissue repair, secretion of pro/anti-inflammatory proteins, phagocytosis, antigen presentation, and stimulation of mucus production ( Joshi et al, 2018 ) as well as in the polarization of innate and adaptive immunity ( Armstrong et al, 2019 ). Macrophage activation in response to PAMPs depends on the PRRs recognizing specific PAMPs, such as lipopolysaccharide (LPS) from Gram-negative bacteria by TLR4 or viral double-stranded RNA (dsRNA) by TLR3 or RIG-I, to activate signaling pathways leading to the induction of the immune transcriptional program ( Escoubet-Lozach et al, 2011 ; Liu et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…AM are an important defense cell when viral or bacterial organisms invade deep into the lung to orchestrate the initiation and resolution of the immune response. AM maintain various effector functions, such as tissue repair, secretion of pro/anti-inflammatory proteins, phagocytosis, antigen presentation, and stimulation of mucus production ( Joshi et al, 2018 ) as well as in the polarization of innate and adaptive immunity ( Armstrong et al, 2019 ). Macrophage activation in response to PAMPs depends on the PRRs recognizing specific PAMPs, such as lipopolysaccharide (LPS) from Gram-negative bacteria by TLR4 or viral double-stranded RNA (dsRNA) by TLR3 or RIG-I, to activate signaling pathways leading to the induction of the immune transcriptional program ( Escoubet-Lozach et al, 2011 ; Liu et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although this analysis suggested that the cell populations obtained through the two protocols were very similar, comparison of the global mean β values significantly differed between SI and BAL. Through exploration of a previous study's finding [5] that designated unique CpG signatures to macrophages collected from the upper or lower parts of the lungs, we examined the possibility that this slight discrepancy was related to the local pulmonary site of sample collection. Indeed, the analysis allowed prediction of the site of collection (either upper or lower lung or in one case a mixture of both).…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of cells derived from the upper and/or lower lungs was identified by using extracted CpGs from the HLA-DR datasets as test data while using the Armstrong et al data[5] as training data sets in…”
mentioning
confidence: 99%
“…Right upper lobe lung macrophages were used in this study, as several studies have shown that the right upper lobe is the predominant lung lobe affected in CF patients (26,35), and our previous work has shown regional differences in the phenotype of lung macrophages (36,37). Cells were plated in six-well tissue culture dishes seeded at 1 3 10 6 cells per well.…”
Section: Experimental Design and Gene Expressionmentioning
confidence: 99%